RAPD-PCR ANALYSIS OF FRESH WATER FISH SPECIES IN THREE RESERVOIRS OF NORTH MAHARASHTRA, INDIA - DHANGAR, SAGAR D.; LOHAR, PRAKASH S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Assessment of genetic variation among the carp fishes captured from rivers of north Maharashtra is prime objective of the present study. The genetic variability among fresh water carp fish belonging to family Cyprinidae inhabiting three reservoirs of Maharashtra was examined in department of Zoology using random amplified polymorphic DNA (RAPD) during February 2018 to January 2019. Scale samples of each test fish were processed for extraction of genomic DNA. Ten Oligonucleotide primers were screened and three primers were selected to amplify DNA of test fish. Three out of 10 primers were good candidate for developing molecular markers. Using pattern analysis of polymorphic and monomorphic bands generated by three primers in 70 carp fish belonging to 24 genera of Cyprinidae family phylogenetic tree constructed. This study represents a first step towards the generation of DNA markers for species diagnosis and assessment of genetic diversity of economically important carp fish species.